(METH)acrylic graft copolymer, epoxy resin composition, adhesive, cured product, molding material and fiber-reinforced plastic

By introducing (meth)acrylic graft copolymer into epoxy resin and the side chain contains specific groups, the bonding strength and impact strength of the epoxy resin are improved, and the problem of insufficient toughness of epoxy resin materials is solved, and it is suitable for a variety of complex applications.

JP2025018794APending Publication Date: 2025-02-06MITSUBISHI CHEM CORP

Patent Information

Application Number
JP2023122796
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

In the prior art, the toughness and bonding strength of the epoxy resin material are insufficient, making it difficult to meet high-demand application scenarios.

Method used

The (meth)acrylic graft copolymer containing the main chain and side chain structure is used, and the side chain contains hydroxyl groups, alkoxy groups and cyclic ether groups, combined with epoxy resin and hardener to form a cured product with high bonding strength and high impact strength.

Benefits of technology

It achieves high bonding strength and high impact strength cured products, suitable for applications in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018794000001
    Figure 2025018794000001
  • Figure 2025018794000002
    Figure 2025018794000002
  • Figure 2025018794000003
    Figure 2025018794000003
Patent Text Reader

Abstract

To provide a (meth)acrylic graft copolymer which enables provision of a cured product having high adhesive strength and impact strength, an epoxy resin composition containing the (meth)acrylic graft copolymer, a cured product of the same, an adhesive, a molding material and a fiber-reinforced plastic.SOLUTION: An epoxy resin composition has a main chain polymer structure and a side chain polymer structure, wherein the side chain polymer structure contains at least one of a hydroxyl group and an alkoxy group, and a cyclic ether group. An epoxy resin composition contains the (meth)acrylic graft copolymer, an epoxy resin (B) and a curing agent (C).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a (meth)acrylic graft copolymer, an epoxy resin composition, an adhesive, a cured product, a molding material, and a fiber-reinforced plastic. [Background technology]

[0002] Epoxy resins are excellent in rigidity, heat resistance, electrical properties, durability, etc., and are therefore used in adhesives and molding materials such as vehicle structural adhesives, civil engineering and construction adhesives, adhesives for electronic materials, industrial adhesives, fiber-reinforced plastics, etc. On the other hand, epoxy resins are generally known to be brittle, and studies are being conducted to improve adhesive strength and impact strength by improving toughness.

[0003] For example, Patent Document 1 discloses that a cured product having excellent adhesive strength and impact strength can be obtained from an epoxy resin composition containing an epoxy resin and a (meth)acrylic polymer having a structural unit derived from a macromonomer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2019 / 049951 Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention aims to provide a (meth)acrylic graft copolymer that can give a cured product having high adhesive strength, an epoxy resin composition containing the (meth)acrylic graft copolymer, an adhesive, a cured product, a molding material, and a fiber-reinforced plastic thereof. Another aim of the present invention is to provide a (meth)acrylic graft copolymer that can give a cured product having high impact strength, an epoxy resin composition containing the (meth)acrylic graft copolymer, an adhesive, a cured product, a molding material, and a fiber-reinforced plastic thereof. [Means for solving the problem]

[0006] The present invention includes the following configurations. [1] A (meth)acrylic graft copolymer having a main chain polymer structure and a side chain polymer structure, the side chain polymer structure containing at least one of a hydroxyl group and an alkoxy group, and a cyclic ether group. [2] The (meth)acrylic graft copolymer according to [1] above, wherein the side chain polymer structure contains at least one of a structural unit derived from a (meth)acrylate (a1) having a hydroxyl group and a structural unit derived from a (meth)acrylate (a2) having an alkoxy group, and a structural unit derived from a (meth)acrylate (a3) ​​having a cyclic ether group. [3] The (meth)acrylic graft copolymer according to [2] above, wherein the (meth)acrylate (a1) having a hydroxyl group is a (meth)acrylate represented by the following formula (1): CH2=CR 1 COO(R 2 O) n1 -H (1) (In formula (1), R 1 is H or CH3, R 2 is C2H4, C3H6, or C4H8, and n1 is an integer from 1 to 15. [4] The (meth)acrylic graft copolymer according to [2] above, wherein the (meth)acrylate (a2) having an alkoxy group is a (meth)acrylate represented by the following formula (2): CH2=CR 3 COO(R 4 O) n2 R 5 (2) (In formula (2), R 3 is H or CH3, R 4 is C2H4, C3H6, or C4H8, R 5 represents an alkyl group having 1 to 8 carbon atoms or a phenyl group, and n2 represents an integer of 1 to 15. [5] The (meth)acrylic graft copolymer according to any one of the above [1] to [4], which contains a structural unit derived from a macromonomer (M) and a structural unit derived from a vinyl radically polymerizable monomer (m1). [6] The (meth)acrylic graft copolymer according to [5] above, wherein the macromonomer (M) contains a structural unit derived from a vinyl radically polymerizable monomer (m2). [7] The (meth)acrylic graft copolymer according to [6] above, wherein the macromonomer (M) contains a structure represented by the following formula (3):

[0007] [ka]

[0008] (In formula (3), X 1 ~X n-1 are each independently H, CH3, or CH2OH; Y 1 ~Y n are each independently a substituent bonded to a vinyl group of the vinyl radical polymerizable monomer (m2), Z is a terminal group, and n is an integer of 2 to 10,000. [8] An epoxy resin composition comprising the (meth)acrylic graft copolymer according to any one of the above [1] to [7], an epoxy resin (B), and a curing agent (C). [9] The epoxy resin composition according to [8], further comprising a polymer (D) having a core-shell structure.

[10] An adhesive containing the epoxy resin composition according to [8] or [9] above.

[11] A cured product of the epoxy resin composition according to [8] or [9] above.

[12] A molding material comprising the cured product according to

[11] above.

[13] A fiber-reinforced plastic comprising the cured product according to

[11] above. Effect of the Invention

[0009] According to the present invention, there are provided a (meth)acrylic graft copolymer that can give a cured product having high adhesive strength, an epoxy resin composition containing the (meth)acrylic graft copolymer, an adhesive, a cured product, a molding material, and a fiber-reinforced plastic thereof. Also, according to the present invention, there are provided a (meth)acrylic graft copolymer that can give a cured product having high impact strength, an epoxy resin composition containing the (meth)acrylic graft copolymer, an adhesive, a cured product, a molding material, and a fiber-reinforced plastic thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below. The following embodiments are merely examples for explaining the present invention, and are not intended to limit the present invention to these embodiments. The present invention can be implemented in various forms without departing from the spirit of the present invention.

[0011] In the present invention, "(meth)acrylic" is a general term for "acrylic" and "methacrylic". "(meth)acrylate" is a general term for "acrylate" and "methacrylate". "(meth)acryloyl group" is a general term for "acryloyl group" and "methacryloyl group", and is a group represented by CH2=C(R)-C(=O)- (R is a hydrogen atom or a methyl group). "Macromonomer" means a high molecular weight compound having a radical polymerizable group or an addition-reactive functional group. The number average molecular weight (Mn) is usually 1000 to 1,000,000. "Vinyl radical polymerizable monomer" means a monomer having an ethylenically unsaturated bond that is not a macromonomer.

[0012] [Epoxy resin composition] The epoxy resin composition of the present invention contains a (meth)acrylic graft copolymer (A) (hereinafter also referred to as "component (A)"), an epoxy resin (B) (hereinafter also referred to as "component (B)"), and a curing agent (C) (hereinafter also referred to as "component (C)"). The epoxy resin composition of the present invention may further contain a polymer (D) having a core-shell structure (hereinafter also referred to as "component (D)"). In addition, the epoxy resin composition of the present invention may contain components other than components (A) to (D) (hereinafter also referred to as "optional components") as necessary, within the scope of not impairing the effects of the present invention.

[0013] <Component (A)> The component (A) is a (meth)acrylic graft copolymer. The (meth)acrylic graft copolymer (A) has a main chain polymer structure and a side chain polymer structure, and the side chain polymer structure contains at least one of a hydroxyl group and an alkoxy group, and a cyclic ether group. The (meth)acrylic graft copolymer (A) preferably has a side chain polymer structure that contains at least one of a structural unit derived from a (meth)acrylate (a1) having a hydroxyl group (hereinafter also referred to as "component (a1)") and a structural unit derived from a (meth)acrylate (a2) having an alkoxy group (hereinafter also referred to as "component (a2)"), and a structural unit derived from a (meth)acrylate (a3) ​​having a cyclic ether group (hereinafter also referred to as "component (a3)"). Hereinafter, the structural unit derived from the component (a1) is also referred to as the "structural unit (a1)", and the same applies to structural units derived from the other components.

[0014] From the viewpoint of improving the solubility of the (A) component in the (B) component and improving the adhesive strength and impact resistance of the cured product, the (A) component preferably contains at least one of the structural units (a1) and (a2) in an amount of 1% by mass or more, and more preferably 2% by mass or more, relative to 100% by mass of the total amount of the (A) component. The total content of the structural units (a1) and (a2) in the (A) component is not particularly limited, but is preferably 40% by mass or less, more preferably 30% by mass or less, and particularly preferably 20% by mass or less, relative to 100% by mass of the total amount of the (A) component. The component (A) may be used alone or in combination of two or more types.

[0015] The component (a1) is preferably a (meth)acrylate having a hydroxyl group represented by the following formula (1). CH2=CR 1 COO(R 2 O) n1 -H (1) (In formula (1), R 1 is H or CH3, R 2 is C2H4, C3H6, or C4H8, and n1 is an integer from 1 to 15.

[0016] R 2 C3H6 and C4H8 may be linear or branched. Examples of the (a1) component include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, and polypropylene glycol mono(meth)acrylate. The component (a1) may be used alone or in combination of two or more types.

[0017] As the (a1) component, from the viewpoints of improving the solubility of the (A) component in the (B) component and improving the adhesive strength and impact resistance of the cured product, n1 is preferably 1 to 5, and 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, or 4-hydroxybutyl (meth)acrylate is more preferable, and 2-hydroxyethyl (meth)acrylate or 2-hydroxypropyl (meth)acrylate is even more preferable.

[0018] The component (a2) is preferably a (meth)acrylate having an alkoxy group represented by the following formula (2). CH2=CR 3 COO(R 4 O) n2 R 5 (2) (In formula (2), R 3 is H or CH3, R 4 is C2H4, C3H6, or C4H8, R 5 represents an alkyl group having 1 to 8 carbon atoms or a phenyl group, and n2 represents an integer of 1 to 15.

[0019] R 4 C3H6 and C4H8 may be linear or branched. Examples of the (a2) component include methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, 2-ethylhexyloxyethyl (meth)acrylate, methoxydiethylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, butoxydiethylene glycol (meth)acrylate, 2-ethylhexyloxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, ethoxypolypropylene glycol (meth)acrylate, butoxypolyethylene glycol (meth)acrylate, butoxypolypropylene glycol (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, phenoxypolypropylene glycol (meth)acrylate, and the like. The component (a2) may be used alone or in combination of two or more types.

[0020] As the component (a2), n2 is preferably 1 to 5, from the viewpoint of improving the solubility of the component (A) in the component (B) and improving the adhesive strength and impact resistance of the cured product. 3 is more preferably H or an alkyl group having 1 to 8 carbon atoms, and further preferably methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, 2-ethylhexyloxyethyl (meth)acrylate, methoxydiethylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, butoxydiethylene glycol (meth)acrylate, or 2-ethylhexyloxydiethylene glycol (meth)acrylate.

[0021] The component (a3) ​​is a (meth)acrylate having a cyclic ether group. The cyclic ether group is preferably a 3- to 6-membered ring, more preferably a 3- to 5-membered ring. Examples of the (meth)acrylate (a3) ​​having a cyclic ether group include tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, (meth)acryloylmorpholine, (3,4-epoxycyclohexyl)methyl (meth)acrylate, β-methylglycidyl (meth)acrylate, (3-ethyloxetan-3-yl)methyl (meth)acrylate, (2-methyl-2-ethyl-1,3-dioxolan-4-yl) (meth)acrylate, (5-ethyl-1,3-dioxan-5-yl)methyl (meth)acrylate, and (2-oxo-1,3-dioxolan-4-yl)methyl (meth)acrylate. The component (a3) ​​may be used alone or in combination of two or more types.

[0022] As the component (a3), glycidyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, (3,4-epoxycyclohexyl)methyl (meth)acrylate, β-methylglycidyl (meth)acrylate, and (2-oxo-1,3-dioxolan-4-yl)methyl (meth)acrylate are more preferred, and glycidyl (meth)acrylate is even more preferred, because they can react with the curing agent (C) to provide particularly good adhesive strength and impact resistance.

[0023] From the viewpoint of obtaining good adhesive strength and impact resistance of the cured product, the content of the structural unit (a3) ​​in the component (A) is preferably 1 to 50 mass%, more preferably 2 to 40 mass%, and even more preferably 3 to 30 mass%, relative to 100 mass% total mass of the component (A).

[0024] The component (A) is a graft copolymer and is not particularly limited as long as it has a branched structure in which a side chain polymer is bonded to a main chain polymer, but it preferably contains a constituent unit derived from a vinyl radically polymerizable monomer (m1) (hereinafter also referred to as "component (m1)") and a constituent unit derived from a macromonomer (M) (hereinafter also referred to as "component (M)"). Examples of the (m1) component include the (a1) to (a3) ​​components, as well as monofunctional (meth)acrylates, polyfunctional (meth)acrylates, and other vinyl compounds (hereinafter also referred to as "other vinyl compounds").

[0025] Specific examples of monofunctional (meth)acrylates include (meth)acrylic acid, (meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl maleate, 2-(meth)acryloyloxyethyl phthalate, and 2-(meth)acryloyloxyethyl hexahydrophthalate, and other (meth)acrylates containing a carboxyl group; cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclopentene. (Meth)acrylates having a cycloalkyl group, such as dicyclopentenoxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, adamantyl (meth)acrylate, and 1,4-cyclohexanedimethanol monoacrylate; phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, and phenoxypolyethylene glycol (meth)acrylate; (meth)acrylates having an aryl group such as nonylphenoxy polyethylene glycol (meth)acrylate, phenoxy polypropylene glycol (meth)acrylate, phenylphenyl (meth)acrylate, phenylphenoxyethyl (meth)acrylate, phenoxybenzyl (meth)acrylate, phenylbenzyl (meth)acrylate, naphthyl (meth)acrylate, and (1-naphthyl)methyl (meth)acrylate; (meth)acrylates having an isocyanate group such as 2-isocyanatoethyl (meth)acrylate, 2-isocyanatopropyl (meth)acrylate, 3-isocyanatopropyl (meth)acrylate, 2-(2-(meth)acryloyloxyethyloxy)ethyl isocyanate, and 1,1-(bis(meth)acryloyloxymethyl)ethyl isocyanate; (meth)acrylamides such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, and N,N-diethyl(meth)acrylamide;Examples of the silane include 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 2-(meth)acryloyloxyethyl acid phosphate, trifluoroethyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and diethylaminoethyl (meth)acrylate. These monofunctional (meth)acrylates may be used alone or in combination of two or more kinds.

[0026] Specific examples of polyfunctional (meth)acrylates include ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, polybutylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, polycarbonate diol di(meth)acrylate, polyester diol di(meth)acrylate, bisphenol A ethylene oxide adduct di(meth)acrylate, bisphenol A dimeth ... Examples of the functional (meth)acrylate include difunctional (meth)acrylates such as propylene oxide adduct di(meth)acrylate of terephthalic acid A, polyurethane di(meth)acrylate, and 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene; trifunctional (meth)acrylates such as trimethylolpropane tri(meth)acrylate, ethoxylated isocyanuric acid tri(meth)acrylate, and ε-caprolactone-modified tris((meth)acryloxyethyl)isocyanurate; tetrafunctional (meth)acrylates such as ditrimethylolpropane tetra(meth)acrylate; pentafunctional (meth)acrylates such as dipentaerythritol penta(meth)acrylate; and hexafunctional (meth)acrylates such as dipentaerythritol hexa(meth)acrylate. These polyfunctional (meth)acrylates may be used alone or in combination of two or more kinds.

[0027] The other vinyl-based compound is not particularly limited as long as it is copolymerizable with the monofunctional (meth)acrylate and the polyfunctional (meth)acrylate, and examples thereof include styrene or styrene derivatives such as styrene, α-methylstyrene, pt-butylstyrene, vinyltoluene, etc.; unsaturated carboxylic acids such as itaconic acid, maleic acid, fumaric acid, etc.; unsaturated nitriles such as (meth)acrylonitrile, etc.; unsaturated carboxylic acid esters such as diethyl maleate, dibutyl maleate, dibutyl fumarate, diethyl itaconate, dibutyl itaconate, etc.; and vinyl esters such as vinyl acetate, vinyl propionate, etc. The other vinyl compounds may be used alone or in combination of two or more kinds.

[0028] As the (m1) component, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, and butoxyethyl (meth)acrylate are preferred, since they improve the solubility of the (A) component in the (B) component and can improve the adhesive strength and impact resistance of the cured product. Ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, methoxyethyl (meth)acrylate, and ethoxyethyl (meth)acrylate are more preferred.

[0029] The macromonomer (M) is a high molecular weight compound having a radically polymerizable group or an addition-reactive functional group, and its number average molecular weight (Mn) is usually 1,000 to 100,000.

[0030] The component (M) is not particularly limited as long as it is a high molecular weight compound having a radically polymerizable group or an addition-reactive functional group, but from the standpoint of high degree of design for the solubility of the component (A) in the component (B), it is preferably a compound containing a structural unit derived from a vinyl radically polymerizable monomer (m2) (hereinafter also referred to as "component (m2)"), and more preferably a compound containing two or more structural units derived from the component (m2) and having a radically polymerizable group at its terminal. The component (M) may be used alone or in combination of two or more types.

[0031] As the component (m2), the above-mentioned components (a1) to (a3) ​​and other compounds exemplified as vinyl radical polymerizable monomers can be used.

[0032] From the standpoint of the solubility of the component (A) in the component (B), it is preferable to contain at least one of the components (a1) and (a2) as the component (m2).

[0033] From the viewpoint of the solubility of the component (A) in the component (B), it is preferable that the component (m2) contains the component (a3), and glycidyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, (3,4-epoxycyclohexyl)methyl (meth)acrylate, β-methylglycidyl (meth)acrylate, or (2-oxo-1,3-dioxolan-4-yl)methyl (meth)acrylate is more preferable, and glycidyl (meth)acrylate is even more preferable.

[0034] The component (M) preferably has a structure represented by the following formula (3) from the viewpoint of excellent radical polymerizability with the component (m1).

[0035] [ka]

[0036] In formula (3), X 1 ~X n-1 are each independently H, CH3, or CH2OH; Y1 ~Y n are each independently a substituent bonded to the vinyl group of the vinyl radically polymerizable monomer (m2), Z is a terminal group, and n is an integer of 2 to 10,000. In addition, "-···-" in formula (3) represents a state in which the monomer units are polymerized.

[0037] X 1 ~X n-1 is preferably a methyl group, and from the viewpoint of ease of synthesis, it is preferable that half or more of the groups are methyl groups. Y 1 ~Y n Each of X bonded to a vinyl group of the vinyl radical polymerizable monomer (m2) independently represents 1 ~X n-1 Examples of such substituents include OR 6 , halogen atom, COR 7 , COOR 8 , C.N., C.O.N. 9 R 10 , N.H.C.O.R. 11 , or R 12 In addition, R 6 ~R 12 are each independently a hydrogen atom, an alkyl group, a cycloalkyl group, a cyclic ether group, an aryl group, a heteroaryl group, or the like. Z is a terminal group. The terminal group may be a hydrogen atom or a group derived from a radical polymerization initiator, as in the case of a terminal group of a polymer obtained by known radical polymerization. n means the number of monomer units in one molecule of the macromonomer (M), and is an integer of 2 to 10,000, preferably an integer of 5 to 1,000, and more preferably an integer of 10 to 500.

[0038] The number average molecular weight (Mn) of the component (M) is preferably from 1,000 to 30,000, more preferably from 1,000 to 20,000, and even more preferably from 1,000 to 10,000. When the number average molecular weight of the component (M) is within the above range, the solubility of the component (A) in the component (B) is improved. The mass average molecular weight (Mw) of the component (M) is preferably from 1,000 to 100,000, more preferably from 1,000 to 50,000, and even more preferably from 1,000 to 30,000. When the mass average molecular weight of the component (M) is within the above range, the solubility of the component (A) in the component (B) becomes better. The Mw / Mn of the component (M) is preferably from 1 to 5, and more preferably from 1.5 to 3. When the Mw / Mn of the component (M) is within the above range, the solubility of the component (A) in the component (B) becomes better. The number average molecular weight (Mn) and weight average molecular weight (Mw) of the component (M) are each values ​​calculated as polystyrene equivalents measured by gel permeation chromatography (GPC).

[0039] The component (M) may be one produced by a known method, or a commercially available product. Examples of methods for producing the component (M) include a production method using a cobalt chain transfer agent (U.S. Pat. No. 4,680,352, etc.), a method using an α-substituted unsaturated compound such as α-bromomethylstyrene as a chain transfer agent (WO 1988 / 04304), a method in which a polymerizable group is chemically bonded (JP-A-60-133007 and U.S. Pat. No. 5,147,952, etc.), and a method using thermal decomposition (JP-A-11-240854, etc.). The method of producing component (M) is preferably a method using a cobalt chain transfer agent, since it requires fewer production steps and uses a catalyst with a high chain transfer constant. Because the cobalt chain transfer agent has a high chain transfer constant, it is possible to obtain component (M) with a controlled molecular weight by adding a small amount of the agent.

[0040] As the cobalt chain transfer agent, a known cobalt complex can be used. The amount of the cobalt chain transfer agent used is preferably 0.00001 to 0.1 parts by mass, more preferably 0.00005 to 0.05 parts by mass, and even more preferably 0.0001 to 0.02 parts by mass, per 100 parts by mass of the component (m2).

[0041] The component (A) and the macromonomer (M) can be produced by known methods such as solution polymerization, suspension polymerization, emulsion polymerization, and redox polymerization.

[0042] From the viewpoint of improving the solubility of the component (A) in the component (B) and improving the adhesive strength and impact resistance of the cured product, the content of the structural unit (M) component in the component (A) is preferably 0 to 60 mass%, more preferably 1 to 50 mass%, and even more preferably 5 to 40 mass%, relative to 100 mass% of the total amount of the component (A).

[0043] The mass average molecular weight (Mw) of component (A) is preferably 10,000 to 1,000,000, more preferably 20,000 to 800,000, and even more preferably 30,000 to 600,000. When the mass average molecular weight of component (A) is within the above range, the solubility of component (A) in component (B) becomes better. The number average molecular weight (Mn) of component (A) is preferably from 3,000 to 300,000, more preferably from 50,000 to 200,000, and even more preferably from 10,000 to 100,000. When the number average molecular weight of component (A) is within the above range, the solubility of component (A) in component (B) becomes better. The Mw / Mn of component (A) is preferably from 1 to 20, and more preferably from 1.5 to 15. When the Mw / Mn of component (A) is within the above range, the solubility of component (A) in component (B) becomes better. The number average molecular weight (Mn) and weight average molecular weight (Mw) of the component (A) are each values ​​calculated as polystyrene equivalents measured by gel permeation chromatography (GPC).

[0044] <(B) component> Component (B) is an epoxy resin. Examples of the component (B) include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AD ​​type epoxy resins, bisphenol E type epoxy resins, naphthalene type epoxy resins, biphenyl type epoxy resins, dicyclopentadiene type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins, and glycidylamine type epoxy resins. Examples of the component (B) include prepolymers of the above-mentioned epoxy resins, copolymers of the above-mentioned epoxy resins with other polymers, such as polyether-modified epoxy resins and silicone-modified epoxy resins, and those in which a portion of the above-mentioned epoxy resins has been substituted with a reactive diluent having an epoxy group.

[0045] Examples of reactive diluents include monoglycidyl compounds such as resorcinol glycidyl ether, t-butylphenyl glycidyl ether, 2-ethylhexyl glycidyl ether, allyl glycidyl ether, phenyl glycidyl ether, 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl methyl dimethoxysilane, 1-(3-glycidoxypropyl)-1,1,3,3,3-pentamethylsiloxane, and N-glycidyl-N,N-bis[3-(trimethoxysilyl)propyl]amine; and monoalicyclic epoxy compounds such as 2-(3,4)-epoxycyclohexyl)ethyltrimethoxysilane. These reactive diluents may be used alone or in combination of two or more.

[0046] As component (B), bisphenol A type epoxy resins and bisphenol F type epoxy resins are preferred because they are liquid and easy to handle, and because they have high glass transition points and thus increase the adhesive strength of the cured product. These components (B) may be used alone or in combination of two or more.

[0047] <(C) component> The component (C) is a component that cures the component (B) and is used to adjust the curability and properties of the cured product of the epoxy resin composition. As the component (C), known compounds can be used, such as acid anhydrides, amine compounds, phenol compounds, and latent hardeners.

[0048] Specific examples of the component (C) include acid anhydrides such as phthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, trialkyltetrahydrophthalic anhydride, methylhimic anhydride, methylcyclohexene dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarboxylic anhydride, ethylene glycol bistrimellitate, glycerol tristrimellitate, dodecenyl succinic anhydride, polyazelaic anhydride, and poly(ethyloctadecanedioic) anhydride;2,5(2,6)-bis(aminomethyl)bicyclo[2,2,1]heptane, isophoronediamine, ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, diethylaminopropylamine, bis(4-amino-3-methyldicyclohexyl)methane, diaminodicyclohexylmethane, bis(aminomethyl)cyclohexane, bis(aminomethyl)norbornane, bis(4-aminocyclohexyl)methane, metaphenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, diaminodiethyldiphenylmethane, diethyltoluenediamine, diaminodiphenylsulfones such as 3,3'-diaminodiphenylsulfone (3,3'-DDS), 4,4'-diaminodiphenylsulfone (4,4'-DDS), diaminodiphenylether (DADPE), bisaniline, dimethylaniline, triethylenediamine, dimethylbenzylamine, 2,4,6-tris(dimethylaminomethyl)phenylamine, amine compounds such as phenol, benzyldimethylaniline, 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), 4,4'-diaminodiphenylmethane, 2,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 2,2'-diaminobiphenyl, 3,3'-diaminobiphenyl, 2,4-diaminophenol, 2,5-diaminophenol, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, m-xylylenediamine, 2,3-tolylenediamine, 2,4-tolylenediamine, 2,5-tolylenediamine, 2,6-tolylenediamine, 3,4-tolylenediamine, methylthiotoluenediamine, diethyltoluenediamine, and dicyandiamide; phenol compounds such as phenol novolac resin, cresol novolac resin, bisphenol A, bisphenol F, bisphenol AD, and diallylated derivatives of these bisphenols;Carbohydrazide, oxalic acid dihydrazide, malonic acid dihydrazide, succinic acid dihydrazide, iminodiacetic acid dihydrazide, adipic acid dihydrazide, pimelic acid dihydrazide, suberic acid dihydrazide, azelaic acid dihydrazide, sebacic acid dihydrazide, dodecane dihydrazide, hexadecane dihydrazide, maleic acid dihydrazide, fumaric acid dihydrazide, diglycol Examples of hydrazide compounds include carboxylic acid dihydrazide, tartaric acid dihydrazide, malic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, 2,6-naphthoic acid dihydrazide, 4,4'-bisbenzenedihydrazide, 1,4-naphthoic acid dihydrazide, Amicure VDH, Amicure UDH (all trade names, manufactured by Ajinomoto Co., Inc.), and citric acid trihydrazide; Among these, from the viewpoint of improving the storage stability of the epoxy resin composition, the component (C) is preferably an amine compound or a hydrazide compound, and more preferably dicyandiamide or a hydrazide compound. These components (C) may be used alone or in combination of two or more.

[0049] <(D) component> Component (D) is a polymer having a core-shell structure. By adding component (D), the adhesive strength and impact strength of the cured product can be further increased. The structure of component (D) is preferably such that the core layer is one or more selected from the group consisting of diene-based rubber polymers, acrylic-based rubber polymers, and organosiloxane-based rubber polymers, and the shell layer is a vinyl-based polymer.

[0050] An example of the diene rubber polymer is a copolymer of 1,3-butadiene, a vinyl monomer copolymerizable therewith, and a crosslinkable monomer used as required. For ease of blending with component (B), component (D) is preferably handled as an "epoxy dispersion of component (D)" obtained by removing water and emulsifier from latex and replacing them with epoxy resin.

[0051] A commercially available product may be used as the epoxy dispersion liquid of component (D). An example of the commercially available product is Kane Ace MX Series manufactured by Kaneka Corporation. Kane Ace MX154, an example of the Kane Ace MX Series, is a dispersion liquid in which a polymer component (about 40% by mass) whose core layer is polybutadiene and whose shell layer is a vinyl polymer is dispersed as a single particle in bisphenol A type epoxy resin (about 60% by mass).

[0052] <Optional ingredients> Optional components include, for example, 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU), 2-methylimidazole, 2-ethyl-4-methylimidazole, adducts of imidazole compounds and epoxy resins, triphenylphosphine, tetraphenylphosphine tetraphenylborate, diazabicycloundecene (DBU) and other curing accelerators; 2,6-di-t-butylphenol, 2,6-di-t-butyl-p-cresol, n-octadecyl-3-(3',5'- Di-t-butyl-4'-hydroxyphenyl)propionate, tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane, triethylene glycol bis[3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,6-hexanediol bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], triethyl phosphite, tri(2-ethylhexyl)phosphite , tridecyl phosphite, triphenyl phosphite, tris isodecyl phosphite, tris tridecyl phosphite, tris (2,4-di-t-butylphenyl) phosphite, dihexyl sulfide, dilauryl-3,3'-thiodipropionate, ditridecyl-3,3'-thiodipropionate, dimyristyl-3,3'-thiodipropionate, distearal-3,3'-thiodipropionate, pentaerythritol tetrakis (β-lauryl thiopropionate) Examples of the additives include antioxidants such as silicone oil, natural wax, and synthetic wax; release agents such as glass beads, crystalline silica, fused silica, calcium silicate, alumina, and calcium carbonate; fibers such as glass fiber, carbon fiber, alumina fiber, and cellulose nanofiber; flame retardants such as antimony trioxide; halogen trapping agents such as hydrotalcite and rare earth oxides; colorants such as carbon black and red iron oxide; silane coupling agents; defoamers; rheology adjusters: pigments; dyes, etc. These optional components may be used alone or in combination of two or more.

[0053] <Content> When the total mass of the components (A) to (D) is taken as 100 mass %, the preferred content of each component in the epoxy resin composition is as follows. The content of the component (A) is preferably 1 to 60 mass%, more preferably 5 to 55 mass%, and even more preferably 10 to 50 mass%, because this allows the epoxy resin composition to have a low viscosity with good workability while further increasing the toughness and adhesive strength of the cured product. The content of the (B) component is preferably 20 to 90 mass %, more preferably 30 to 80 mass %, and even more preferably 40 to 70 mass %, because this allows the epoxy resin composition to have a low viscosity and good workability. The content of the (C) component is preferably 0.1 to 10 mass%, more preferably 0.5 to 9 mass%, and even more preferably 1 to 8 mass%, because this provides sufficient curability to obtain a cured product while improving the storage stability of the epoxy resin composition. The content of the (D) component is preferably 0 to 40 mass%, more preferably 1 to 35 mass%, and even more preferably 3 to 30 mass%, because this allows the epoxy resin composition to have a low viscosity with good workability while further increasing the toughness and adhesive strength of the cured product.

[0054] <Manufacturing method> The method for producing the epoxy resin composition is not particularly limited, and known methods can be used. For example, the (A), (B) and (C) components, and optionally the (D) component and optional components may be mixed simultaneously, or some of the components (e.g., the (A) and (B) components) may be mixed in advance, and the mixture may be mixed with the remaining components. The mixing method is not particularly limited, and a known mixer such as a planetary centrifugal mixer, a three-roll mill, or a kneader can be used.

[0055] <Action and effect> The epoxy resin composition of the present invention described above contains the above-mentioned components (A), (B), and (C), and optionally the component (D) and optional components, so that a cured product having high adhesive strength can be obtained. Also, the epoxy resin composition of the present invention contains the above-mentioned components (A), (B), and (C), and optionally the component (D) and optional components, so that a cured product having high impact strength can be obtained.

[0056] <Application> The epoxy resin composition of the present invention is useful as an adhesive since it can give a cured product having high adhesive strength. Also, the epoxy resin composition of the present invention is useful as a molding material and a fiber-reinforced plastic since it can give a cured product having high adhesive strength and high impact strength. The use of the epoxy resin composition of the present invention is not limited to the above. The epoxy resin composition of the present invention can also be used for other purposes, for example, for various purposes in which thermosetting resins such as epoxy resins are used. Examples of such uses include paints, coating agents, insulating materials, sealants, etc. The adhesive, molding material, and fiber-reinforced plastic containing the epoxy resin composition of the present invention will be described below.

[0057] [glue] The adhesive of the present invention contains the above-mentioned epoxy resin composition of the present invention. Examples of adhesives include adhesives for vehicles including structural adhesives for automobiles, etc., adhesives for civil engineering and construction, adhesives for electronic materials, adhesives for general office use, adhesives for medical instruments, and industrial adhesives. Examples of adhesives for vehicles include hemming adhesives, weld bond adhesives, mastic adhesives, direct glazing adhesives, spot sealers, body sealers, undercoats, and the like. Examples of adhesives for electronic materials include interlayer adhesives for multilayer substrates such as build-up substrates, die bonding agents, adhesives for semiconductors such as underfills, underfills for reinforcing BGAs, and mounting adhesives such as anisotropic conductive films (ACFs) and anisotropic conductive pastes (ACPs). These adhesive applications require high adhesive strength and impact strength.

[0058] [Cured product] The cured product of the present invention is obtained by curing the above-mentioned epoxy resin composition of the present invention. The method for curing the epoxy resin composition is not particularly limited, and any known method can be used, such as a thermal curing method. When the epoxy resin composition is cured by a heat curing method, the optimal conditions vary depending on the type and amount of the component (C) contained in the epoxy resin composition, but it is preferable to cure the epoxy resin composition under heating conditions of, for example, 50 to 250°C for about 0.1 to 10 hours.

[0059] [Molding material] The molding material of the present invention contains the cured product of the above-mentioned epoxy resin composition of the present invention. Examples of the molding material include sheets and films obtained by curing the epoxy resin composition of the present invention. Examples of the molding method include transfer molding and cast molding. Examples of the applications of the molding material include aircraft parts, automobile parts, sporting goods, building materials, electronic circuit boards, semiconductor encapsulants, and reflectors for optical semiconductors. These molding materials are required to have high impact strength.

[0060] [Fiber reinforced plastics] The fiber reinforced plastics (FRP) of the present invention are produced by curing a prepreg in which fibers such as glass fibers or carbon fibers are impregnated with the epoxy resin composition of the present invention. Examples of applications of fiber reinforced plastics include aircraft parts, automobile parts, ship parts, sporting goods, building materials, wind power generation blades, gas tanks, robots, and electronic circuit boards. These fiber reinforced plastics are required to have high impact strength, and the epoxy resin composition that is impregnated therein is required to have high adhesive strength to the fibers. EXAMPLES

[0061] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In each of the following examples, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".

[0062] [Measurement and evaluation methods] <Measurement of molecular weight of macromonomer (M)> The molecular weight of the (M) component was measured using a gel permeation chromatograph (GPC apparatus) (manufactured by Tosoh Corporation, product name "HLC-8320") as follows. The component (M) was dissolved in tetrahydrofuran (THF) to a concentration of 0.2% by mass to prepare a THF solution (1). 10 μL of the above THF solution (1) was injected into a GPC apparatus equipped with a Tosoh column (TSKgel SuperHZM-M (inner diameter 4.6 mm, length 15 cm) x 1, HZM-M (inner diameter 4.6 mm, length 15 cm) x 1, HZ-2000 (inner diameter 4.6 mm, length 15 cm) x 1, TSKguardcolumn SuperHZ-L (inner diameter 4.6 mm, length 3.5 cm) x 1), and the measurement was performed under the conditions of flow rate: 0.35 mL / min, eluent: THF containing dibutylhydroxytoluene (BHT) as a stabilizer, and column temperature: 40 ° C., and the mass average molecular weight (Mw) and number average molecular weight (Mn) were calculated in terms of standard polystyrene.

[0063] <Measurement of Molecular Weight of (Meth)acrylic Graft Copolymer (A)> The molecular weight of the (meth)acrylic graft copolymer (A) was measured using a gel permeation chromatograph (GPC apparatus) (manufactured by Tosoh Corporation, product name "HLC-8320") as follows. The (meth)acrylic graft copolymer (A) was dissolved in tetrahydrofuran (THF) to a concentration of 0.2% by mass to prepare a THF solution (2). 10 μL of the above THF solution (2) was injected into a GPC apparatus equipped with a Tosoh column (2 TSKgel SuperHZM-H (inner diameter 6.0 mm, length 15 cm), 1 TSKguardcolumn SuperHZ-H (inner diameter 4.6 mm, length 3.5 cm)), and measurement was performed under the conditions of a flow rate of 0.5 mL / min, eluent: THF containing BHT as a stabilizer, and column temperature: 40° C., and the mass average molecular weight (Mw) and number average molecular weight (Mn) were calculated in terms of standard polystyrene.

[0064] <Evaluation of adhesive strength> A 25 mm wide x 150 mm long x 0.5 mm thick steel plate (manufactured by Engineering Test Services, product name "JIS G3141, SPCC-SD") was used to hold the portion from one end of one side to 50 mm in the length direction, and the remaining portion was coated with an epoxy resin composition. Another steel plate of the same size was attached to the epoxy resin composition-coated surface, fixed so that the thickness of the epoxy resin composition layer was constant, and heated at 180°C for 30 minutes to cure the epoxy resin composition, thereby obtaining a laminate. The cured epoxy resin composition that protruded from the side of the obtained laminate was scraped off, and the gripping portions of each of the two steel plates were bent at a right angle of 90° toward the outside to obtain a T-shaped test piece. Using a precision universal testing machine (Shimadzu Corporation, product name "Autograph AGX-10kNVD, load cell 1kN), the gripping portion of the obtained test piece was held above and below, and the peel strength was measured at 200 mm / min. The measurement was carried out at 23°C. The average value of the load excluding the first 25 mm and the last 25 mm was taken as the T-peel strength. The T-peel strength was measured for three test pieces, and the average value was calculated to evaluate the adhesive strength. A higher T-peel strength indicates better adhesive strength. A higher T-peel strength indicates better toughness.

[0065] <Impact strength evaluation> In accordance with ISO11343 and JIS K6865, a symmetrical wedge test piece was prepared and the impact strength was measured. Specifically, an epoxy resin composition was applied to a 0.8 mm thick bent steel plate (JIS G3141, SPCC-SD, manufactured by Engineering Test Services Co., Ltd.), and the plate was laminated, and then heated at 180°C for 30 minutes to harden the epoxy resin, thereby obtaining a symmetrical wedge test piece. Using a high-speed tensile tester Hydroshot HITS-T10 (manufactured by Shimadzu Corporation, load cell 10kN), a symmetrical wedge test piece was driven at 2m / sec, and the dynamic cleavage resistance value during the cleavage of a 20 mm wide and 30 mm long epoxy resin cured material was measured. The measurement was performed at 23°C. The average value of the dynamic cleavage resistance value between 25% from the beginning and 10% from the end of the travel distance was taken as the impact strength. The higher the impact strength, the better the toughness.

[0066] [Dispersant] <Synthesis Example 1: Synthesis of Dispersant (1)> In a polymerization apparatus equipped with a stirrer, a cooling tube, a thermometer, and a nitrogen gas inlet tube, 900 parts of deionized water, 60 parts of sodium 2-sulfoethyl methacrylate, 10 parts of potassium methacrylate, and 12 parts of methyl methacrylate (MMA) were placed and stirred, and the temperature was raised to 50°C while replacing the inside of the polymerization apparatus with nitrogen. 0.08 parts of 2,2'-azobis(2-methylpropionamidine) dihydrochloride were added thereto as a polymerization initiator, and the temperature was further raised to 60°C. After the temperature was raised, MMA was continuously dropped at a rate of 0.24 parts / min for 75 minutes using a dropping pump. The reaction solution was kept at 60°C for 6 hours, and then cooled to room temperature to obtain a transparent aqueous solution of dispersant (1) with a solid content of 10%.

[0067] [Chain transfer agent] <Synthesis Example 2: Synthesis of Chain Transfer Agent (1)> In a synthesis apparatus equipped with a stirrer, 1.00 g of cobalt (II) acetate tetrahydrate, 1.93 g of diphenylglyoxime, and 80 mL of diethyl ether previously deoxygenated by nitrogen bubbling were placed under a nitrogen atmosphere and stirred at room temperature for 30 minutes. Then, 10 mL of boron trifluoride diethyl ether complex was added and stirred for an additional 6 hours. The mixture was filtered, the solid was washed with diethyl ether, and vacuum dried for 15 hours to obtain 2.12 g of chain transfer agent (1) as a reddish brown solid.

[0068] <Production Example 1: Production of Macromonomer (M1)> In a polymerization apparatus equipped with a stirrer, a cooling tube, a thermometer, and a nitrogen gas inlet tube, 145 parts of deionized water, 0.1 parts of sodium sulfate, and 0.25 parts of dispersant (1) (solid content 10%) were added and stirred to obtain a uniform aqueous solution. 20 parts of 2-hydroxyethyl methacrylate as component (a1), 30 parts of glycidyl methacrylate as component (a3), 50 parts of methyl methacrylate as component (m2), 0.0040 parts of chain transfer agent (1), and 2 parts of 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, product name "Perocta O") as a polymerization initiator were added to obtain an aqueous suspension. Next, the inside of the polymerization apparatus was replaced with nitrogen, the temperature was raised to 80°C and the reaction was carried out for 3.5 hours, and in order to further increase the polymerization rate, the temperature was raised to 90°C and maintained at that temperature for 1 hour. Thereafter, the reaction liquid was cooled to 40°C to obtain an aqueous suspension containing the macromonomer. This aqueous suspension was filtered through a filter, and the residue remaining on the filter was washed with deionized water, dehydrated, and dried at 40°C for 16 hours to obtain a macromonomer (M1). The molecular weight of the resulting macromonomer (M1) was measured, and the results are shown in Table 1.

[0069] <Production Examples 2 to 8: Production of Macromonomers (M2) to (M8)> Macromonomers (M2) to (M8) were obtained in the same manner as in Production Example 1, except that the components (a1) to (a3), the chain transfer agent (1), and the polymerization initiator used were changed to those shown in Table 1. The molecular weights of the obtained macromonomers are shown in Table 1.

[0070] [Table 1]

[0071] The abbreviations in Table 1 are as follows. HOMA: 2-hydroxyethyl methacrylate (manufactured by Mitsubishi Chemical, trade name "Acryester HO"). HPMA: 2-hydroxypropyl methacrylate (manufactured by Mitsubishi Chemical, product name "Acryester HP"). MTMA: Methoxyethyl methacrylate (manufactured by Mitsubishi Chemical, product name "Acryester MT"). MMA: Methyl methacrylate (manufactured by Mitsubishi Chemical, product name "Acryester M"). GMA: Glycidyl methacrylate (manufactured by Mitsubishi Chemical, product name "Acryester G"). Chain transfer agent (1): The chain transfer agent synthesized in Synthesis Example 2. Perocta O: 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, trade name "Perocta O").

[0072] <Production Example 9: Production of (meth)acrylic graft copolymer (A-1)> In a four-neck flask equipped with a stirrer, a thermometer, a cooling tube, and a nitrogen gas inlet, 45 parts of methyl ethyl ketone (MEK), 15 parts of isopropyl alcohol (IPA), and 20 parts of macromonomer (M1) were placed as initial charge solvents, and the external temperature was raised to 85°C under nitrogen gas aeration while stirring. After the external temperature reached 85°C and the internal temperature stabilized, a mixture consisting of 25 parts of MEK, 80 parts of ethyl acrylate as the (m1) component, and 0.13 parts of benzoyl peroxide (manufactured by NOF Corp., trade name: "Niper BMT-K40") as a polymerization initiator was added dropwise over 3 hours. After holding for 1 hour after the end of the dropwise addition, a mixture consisting of 0.5 parts of 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate (manufactured by NOF Corp., trade name: "Perocta O") as a polymerization initiator and 10 parts of MEK was added over 1 hour. After that, after keeping for 2 hours, MEK was added so that the solid content (ratio of monomer charge amount in (monomer + solvent charge amount)) became 50%, and then cooled to room temperature to obtain an MEK solution of (meth)acrylic graft copolymer (A-1). Note that the monomer composition in Table 2 shows that it contains 20 mass% of macromonomer M1, and the monomers constituting macromonomer M1 are 4 mass% of HOMA, 10 mass% of MMA, and 6 mass% of GMA. The molecular weight of the resulting (meth)acrylic graft copolymer (A-1) was measured, and the results are shown in Table 2.

[0073] <Production Examples 10 to 24: Production of (meth)acrylic graft copolymers (A-2) to (A-16)> Solutions of (meth)acrylic graft copolymers (A-2) to (A-16) were obtained in the same manner as in Production Example 9, except that the type and amount of the (M) component, (m1) component, and the initially charged solvent were changed to those shown in Table 2. The molecular weights of the obtained acrylic graft copolymers (A-2) to (A-16) were measured. The results are shown in Table 2.

[0074] [Table 2]

[0075] The abbreviations in Table 2 are as follows. M1 to M8: Macromonomers produced in Production Examples 1 to 8. · EA: Ethyl acrylate (manufactured by Mitsubishi Chemical Corporation, trade name "Ethyl acrylate"). · n-BA: n-Butyl acrylate (manufactured by Mitsubishi Chemical Corporation, trade name "butyl acrylate"). 2-MTA: 2-Methoxyethyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name "Methoxyethyl acrylate"). ·MEK: Methyl ethyl ketone. ·IPA: Isopropyl alcohol.

[0076] [Example 1] 100 parts of the (meth)acrylic graft copolymer (A-1) solution obtained in Production Example 9 was mixed with 50 parts of bisphenol A type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name "jER828"), and MEK was distilled off under reduced pressure using a vacuum dryer to obtain a (meth)acrylic graft copolymer-containing epoxy resin containing 50 parts of the (meth)acrylic graft copolymer (A-1). A mixing vessel was charged with 32 parts of a (meth)acrylic graft copolymer-containing epoxy resin as components (A) and (B) (breakdown: 16 parts of (meth)acrylic graft copolymer (A-1) and 16 parts of jER828), 18 parts of jER828 as component (B), 4 parts of dicyandiamide as component (C), 30 parts of Kane Ace MX154 (trade name, manufactured by Kaneka Corporation) as components (D) and (B) (breakdown: 12 parts of a polymer having a core-shell structure and 12 parts of a bisphenol A polymer having a core-shell structure). An epoxy resin composition was prepared by adding 18 parts of phenol A type epoxy resin, 0.8 parts of 3-(3,4-dichlorophenyl)-1,1-dimethylurea as a curing accelerator, 15.2 parts of calcium carbonate (manufactured by Shiraishi Calcium Co., Ltd., product name "Whiten B") as a filler, and 0.8 parts of glass beads (manufactured by Potters Ballotini Co., Ltd., product name "J-100") using a stirring and degassing device (manufactured by Thinky Corporation, product name "Awatori Rentaro"). The adhesive strength of the obtained epoxy resin composition was evaluated, and the results are shown in Table 3.

[0077] [Examples 2 to 13, Comparative Examples 1 to 3] Epoxy resin compositions were prepared in the same manner as in Example 1, except that the type of component (A) and the amount of each component were changed to those shown in Tables 3 to 5. The results of the adhesive strength evaluation of the epoxy resin compositions of Examples 2 to 13 and Comparative Examples 1 to 3 are shown in Tables 3 to 5.

[0078] [Example 14] 100 parts of the MEK solution of the (meth)acrylic graft copolymer (A-6) obtained in Production Example 14 was mixed with 50 parts of a bisphenol A type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name "jER828"), and the MEK was distilled off under reduced pressure using a vacuum dryer, thereby obtaining a (meth)acrylic graft copolymer-containing epoxy resin containing 50 parts of the (meth)acrylic graft copolymer (A-6). In a mixing vessel, 60 parts of a (meth)acrylic graft copolymer-containing epoxy resin as components (A) and (B) (breakdown: 30 parts of (meth)acrylic graft copolymer (A-6) and 30 parts of jER828) as component (B), 20 parts of jER828 as component (B), 4 parts of dicyandiamide (manufactured by Mitsubishi Chemical Corporation, trade name "DICY7") as component (C), 0.8 parts of 3-(3,4-dichlorophenyl)-1,1-dimethylurea (manufactured by Hodogaya Chemical Co., Ltd., trade name "DCMU") as a curing accelerator, 15.2 parts of calcium carbonate (manufactured by Shiraishi Calcium Co., Ltd., trade name "Whiten B") as a filler, and 0.8 parts of glass beads (manufactured by Potters Ballotini Co., Ltd., trade name "J-100") were added and mixed using a stirring and degassing device (manufactured by Thinky Corporation, product name "Awatori Rentaro") to prepare an epoxy resin composition. The adhesive strength of the obtained epoxy resin composition was evaluated, and the results are shown in Table 4.

[0079] [Examples 15 to 16, Comparative Examples 4 to 6] Epoxy resin compositions were prepared in the same manner as in Example 14, except that the type of component (A) and the amount of each component were changed to those shown in Tables 4 and 5. The results of the adhesive strength evaluation of the epoxy resin compositions of Examples 15 to 16 and Comparative Examples 4 to 6 are shown in Tables 4 to 5.

[0080] [Table 3] [Table 4] [Table 5]

[0081] The results of the impact strength evaluation carried out on the epoxy resin compositions of Examples 1 to 13 and Comparative Example 1 are shown in Tables 6 to 7.

[0082] [Table 6]

[0083] [Table 7]

[0084] The abbreviations in Tables 3 to 7 are as follows. A-1 to A-16: (meth)acrylic graft copolymers (A) produced in Production Examples 9 to 24. · jER828: Bisphenol A type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name "jER828"). Bisphenol A epoxy: A bisphenol A type epoxy resin contained in the Kaneka Corporation product "Kane Ace MX154." DICY: Dicyandiamide (manufactured by Mitsubishi Chemical Corporation, product name "DICY7"). DCMU: 3-(3,4-dichlorophenyl)-1,1-dimethylurea (manufactured by Hodogaya Chemical Industry Co., Ltd., trade name "DCMU"). · Whiten B: Calcium carbonate (manufactured by Shiraishi Calcium Co., Ltd., product name "Whiten B"). J-100: Glass beads (made by Potters Barotini, product name "J-100"). Polymer component in Kane Ace MX154: A polymer with a core-shell structure contained in Kaneka Corporation's product name "Kane Ace MX154."

[0085] As is clear from Tables 3 to 7, the cured products of the epoxy resin compositions obtained in each Example were excellent in adhesive strength and impact strength. On the other hand, the cured products of the epoxy resin compositions obtained in each of the Comparative Examples were poor in adhesive strength and impact strength. [Industrial Applicability]

[0086] From the epoxy resin composition containing the (meth)acrylic graft copolymer of the present invention, a cured product having high adhesive strength and impact strength can be obtained. Therefore, the epoxy resin composition of the present invention is useful as, for example, adhesives for vehicles such as automobiles, adhesives for civil engineering and construction, adhesives for electronic materials, adhesives for general office use, adhesives for medical use, adhesives for industrial use, molding materials, fiber-reinforced plastics, etc.

Claims

1. A (meth)acrylic graft copolymer having a main chain polymer structure and a side chain polymer structure, the side chain polymer structure containing at least one of a hydroxyl group and an alkoxy group, and a cyclic ether group.

2. The (meth)acrylic graft copolymer according to claim 1, wherein the side chain polymer structure contains at least one of a structural unit derived from a (meth)acrylate (a1) having a hydroxyl group and a structural unit derived from a (meth)acrylate (a2) having an alkoxy group, and a structural unit derived from a (meth)acrylate (a3) ​​having a cyclic ether group.

3. The (meth)acrylic graft copolymer according to claim 2 , wherein the (meth)acrylate (a1) having a hydroxyl group is a (meth)acrylate represented by the following formula (1): CH 2 =CR 1 COO(R 2 O) n1 -H ・・・(1) (In formula (1), R 1 is H or CH 3 , R 2 is C 2 H 4 , C 3 H 6 , or C 4 H 8 , n1 represents an integer from 1 to 15.

4. The (meth)acrylic graft copolymer according to claim 2 , wherein the (meth)acrylate (a2) having an alkoxy group is a (meth)acrylate represented by the following formula (2): CH 2 =CR 3 COO(R 4 O) n2 R 5 ・・・(2) (In formula (2), R 3 is H or CH 3 , R 4 is C 2 H 4 , C 3 H 6 , or C 4 H 8 , R 5 represents an alkyl group having 1 to 8 carbon atoms or a phenyl group, and n2 represents an integer of 1 to 15.

5. The (meth)acrylic graft copolymer according to claim 1 , which contains a structural unit derived from a macromonomer (M) and a structural unit derived from a vinyl radically polymerizable monomer (m1).

6. The (meth)acrylic graft copolymer according to claim 5 , wherein the macromonomer (M) contains a structural unit derived from a vinyl radically polymerizable monomer (m2).

7. The (meth)acrylic graft copolymer according to claim 6 , wherein the macromonomer (M) contains a structure represented by the following formula (3): 【Chemistry 1】 (In formula (3), X 1 ~X n-1 are each independently H, CH 3 or CH 2 OH and Y 1 ~Y n are each independently a substituent bonded to the vinyl group of the vinyl radical polymerizable monomer (m2), Z is a terminal group, and n is an integer of 2 to 10,000.

8. An epoxy resin composition comprising the (meth)acrylic graft copolymer according to claim 1, an epoxy resin (B), and a curing agent (C).

9. The epoxy resin composition according to claim 8, further comprising a polymer (D) having a core-shell structure.

10. An adhesive comprising the epoxy resin composition according to claim 8 or 9.

11. A cured product of the epoxy resin composition according to claim 8 or 9.

12. A molding material comprising the cured product according to claim 11.

13. A fiber-reinforced plastic comprising the cured product according to claim 11.

Citation Information

Patent Citations

  • Macromonomer copolymer, epoxy resin composition, adhesive, molding material and cured product

    WO2019049951A1

Cited By

  • Epoxy resin composition, adhesive, molding material and cured product

    JP2023092511A

  • Epoxy resin composition, cured product, adhesive, molding material and fiber-reinforced plastic

    JP2023092512A